2015
DOI: 10.1007/s11684-015-0388-9
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells in autoimmune diseases

Abstract: Th17 cells are a new subset of CD4(+) T cells involved in the clearance of extracellular pathogens and fungi. Accumulating evidence suggests that Th17 cells and their signature cytokines have a pivotal role in the pathogenesis of multiple autoimmune-mediated inflammatory diseases. Here, we summarize recent research progress on Th17 function in the development and pathogenesis of autoimmune diseases. We also propose to identify new small molecule compounds to manipulate Th17 function for potential therapeutic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 116 publications
1
47
0
2
Order By: Relevance
“…Th17 cells, a new subset of Th cells capable of producing IL17, play a vital role in the formation of several autoimmune-mediated inflammatory diseases, including IBD [83,84] . Current studies demonstrate that miR21 [85] , miR155 [63] , miR301a [86] , miR326 [87] , miR1792 cluster [88] , and miR132/212 cluster [89] act as positive regulators of Th17 differentiation.…”
Section: Mirnas and Th17 Cell Differentiationmentioning
confidence: 99%
“…Th17 cells, a new subset of Th cells capable of producing IL17, play a vital role in the formation of several autoimmune-mediated inflammatory diseases, including IBD [83,84] . Current studies demonstrate that miR21 [85] , miR155 [63] , miR301a [86] , miR326 [87] , miR1792 cluster [88] , and miR132/212 cluster [89] act as positive regulators of Th17 differentiation.…”
Section: Mirnas and Th17 Cell Differentiationmentioning
confidence: 99%
“…(Th2; [7]), rheumatoid arthritis, systemic lupus erythematosus, and inflammatory bowel disease (Th17; reviewed in [8]), the influence of the microbiome on the development of T-cell populations has become a major focus. Seminal work by Ivanov et al [9] demonstrated that segmented filamentous bacteria, identified by comparative microbiota profiling, are highly enriched in mice with large numbers of ileal Th17 cells.…”
Section: Key Pointsmentioning
confidence: 99%
“…ϩ T cells, contribute to the pathogenesis of multiple autoimmune and inflammatory diseases, such as systemic lupus erythematosus (SLE), 4 inflammatory bowel disease, rheumatoid arthritis, and ankylosing spondylitis (1). Similar to Th1 and Th2 cells, Th17 cells express retinoic acid-related orphan nuclear receptor ␥t (ROR␥t) as the master regulator, orchestrating the differentiation, maintenance, and function of the Th17 lineage (2).…”
Section: Th17 Cells Which Have Attracted Widespread Attention As a Smentioning
confidence: 99%